MASALAH GALAT PENJEJAKAN MINIMUM PADA SISTEM PENDULUM TERBALIK - BAKHTIAR, T. (School of Data Science, Mathematics and Informatics, IPB University, 2010)
This paper studies the optimal tracking error control problem on an inverted pendulum model. We characterize the optimal tracking error in term of pendulum’s parameters. Particularly, we derive the closed form expression for the pendulum length which gives minimum error. It is shown that the minimum error can always be accomplished as long as the ratio between the mass of the pendulum and that of the cart satisfies a certain constancy, regardless the type of material we use for the pendulum.